2-methoxyestradiol inhibits the malignant behavior of triple negative breast cancer cells by altering their miRNome - Subramani, Ramadevi; Chatterjee, Animesh; Pedroza, Diego A.; Poudel, Seeta; Rajkumar, Preetha; Annabi, Jeffrey; Penner, Elizabeth; Lakshmanaswamy, Rajkumar (Frontiers in Oncology, 2024)
BackgroundTriple-negative breast cancer (TNBC) is a subtype of breast cancer with no effective targeted treatment currently available. Estrogen and its metabolites influence the growth of mammary cancer. Previously, we demonstrated the anti-cancer effects of 2-methoxyestradiol (2ME2) on mammary carcinogenesis.Materials and methodsIn the present study, we investigated the effects of 2ME2 on TNBC cells. TNBC (MDA-MB-231 and MDA-MB-468) and non-tumorigenic breast (MCF10A) cell lines were used to determine the effects of 2ME2 on cell proliferation (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium; MTS assay), cell cycle (flow cytometric assay), migration (transwell migration assay), invasion (matrigel invasion assay), apoptosis (annexin V/propidium iodide assay), colony formation (soft agar assay), and miRNome (human miRNA profiling array). The miRNome data were analyzed using the c-BioPortal and Xena platforms. Moreover, Kyoto Encyclopedia of Genes and Genomes, Gene Ontology, and reactome pathway analyses were performed.ResultsWe found that 2ME2 effectively inhibited cell proliferation and induced apoptosis. Furthermore, 2ME2 treatment arrested TNBC cells in the S-phase of the cell cycle. Treatment with 2ME2 also significantly decreased the aggressiveness of TNBC cells by inhibiting their migration and invasion. In addition, 2ME2 altered the miRNA expression in these cells. In silico analysis of the miRNome profile of 2ME2-treated MDA-MB-468 cells revealed that miRNAs altered the target genes involved in many different cancer hallmarks.Conclusion2ME2 inhibits triple negative breast cancer by impacting major cellular processes like proliferation, apoptosis, metastasis, etc. It further modifies gene expression by altering the miRNome of triple negative breast cancer cells. Overall, our findings suggest 2ME2 as a potent anti-cancer drug for the treatment of TNBC.